Psychological Aspects of Students With Learning Disabilities in E-Environments: A Mini Review and Future Research Directions - Cataudella, Stefania; Carta, Stefano; Mascia, Maria Lidia; Masala, Carmelo; Petretto, Donatella Rita; Penna, Maria Pietronilla (Frontiers in Psychology, 2021)
What are the main learning difficulties or advantages encountered by students with learning disabilities within e-environments? As a result of the Covid-19 emergency, e-learning is being increasingly used to support students’ learning processes. A number of countries closed their schools altogether, so face-to-face lessons were and have been replaced by distance lessons. A search of current literature via Scopus, Eric and Google Scholar electronic databases was conducted according to Prisma Guidelines. Other sources of literature were also considered, starting from the references in the full text of the articles consulted. We used the following search keywords: “learning disabilities” combined with the “AND/OR” Boolean operator and “e-learning platforms”, “well-being”, “psychological factors”, “emotional distress”, “self-regulation”. One body of literature highlights the lack of inclusive accessibility standards and a lack of attention to specific tools for addressing neuropsychological syndromes, which causes students to develop high levels of stress/anxiety and emotional distress, in addition to low levels of well-being, self-esteem and self-efficacy. Another area of literature looks at how students can develop high levels of self-regulation and emotional awareness, as well as high levels of inclusion. Results are discussed in terms of the promotion of e-learning that focuses on the psychological well-being of students and teachers use of technological tools.